Implementation of Regional Regulation of Tabanan Regency Number 11 of 2018 Concerning Tourism Village Related to Increasing Investment Interest in Tabanan Regency - Ni Putu Santya Dewi; I Nyoman Sujana; I Wayan Wesna Astara (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2021)
Tourism that developed in Bali is an important sector for Tabanan Regency in increasing its tourism assets. Formation of Tabanan Regency Regulation No. 11 of 2018 concerning Tourism Villages is a legal umbrella that is expected to be able to increase investment interest in Tabanan Regency. The purpose of this study is to examine the regional regulation of Tabanan regency number 11 of 2018 concerning tourism villages related to increased investment interest in Tabanan regency and to examine the effectiveness of local regulation of Tabanan regency number 11 year 2018 regarding tourism villages related to increased investment interest in Tabanan regency. Furthermore, the method used in this study is empirical legal research method, meanwhile, a sociology approach is an approach used in this study. The results obtained from the study are that the implementation of Tabanan Regency Regulation Number 11 Year 2018 concerning Tourism Villages has been systematic, involving the role of regional apparatus and the community; and Tabanan Regency Regulation Number 11 Year 2018 regarding Tourism Villages related to increased investment interest has not been effective because there are still many obstacles and obstacles found.